Alat Penilaian Disfungsi Penciuman: Tinjauan Sistematis - Dinda Amalia; Heri Kristianto; Rinik Eko Kapti (PERHATI-KL, 2026)
Background: The sense of smell plays a vital role in detecting odors and influences daily functioning and quality of life. Olfactory function can be assessed using subjective approaches, including self-reported questionnaires for individuals with olfactory disorders. Purpose: To summarize and categorize existing olfactory-related scales and questionnaires, based on previous research. Method: A systematic search was conducted following the PRISMA guidelines using ScienceDirect, ProQuest, and PubMed. Studies published between 2014 and 2024 were screened based on predefined criteria, and 10 eligible articles were included. Result: The instruments were classified into three categories: assessment of olfactory function and dysfunction; olfaction-related quality of life; and attitudes, emotional responses, and the perceived importance of smell. Reported reliability values ranged from acceptable to excellent, with Cronbach’s alpha coefficients between 0.65 and 0.98. Olfactory Disorders Questionnaire (ODQ) and the Taste and Smell Tool for Evaluation (TASTE) consist of more than 30 items, and may require longer completion time, which limiting routine clinical use, and provide limited evidence of predictive validity for evaluating the effectiveness of clinical interventions. Conclusion: This review highlighted a wide range of validated olfactory-related questionnaires, emphasizing the affective, emotional, and quality-of-life impacts of olfactory dysfunction. These instruments offer valuable subjective insights, which can complement objective olfactory testing in clinical practice and research